2021
DOI: 10.1002/1873-3468.14170
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the conserved C‐terminal domain of ribosomal P‐proteins impairs the mode of interaction with plant toxins

Abstract: The ribosome is subjected to post‐translational modifications, including phosphorylation, that affect its biological activity. Among ribosomal elements, the P‐proteins undergo phosphorylation within the C terminus, the element which interacts with trGTPases or ribosome‐inactivating proteins (RIPs); however, the role of phosphorylation has never been elucidated. Here, we probed the function of phosphorylation on the interaction of P‐proteins with RIPs using the ribosomal P1‐P2 dimer. We determined the kinetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…Interestingly, fitting the density with a short α-helix satisfies the hydrogen bonding pattern described previously. The observation that the CTD might behave as a random coil or as an α-helix is of significance, and it indicates the possibility for structural rearrangements in this region, as indicated previously ( 28 ).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, fitting the density with a short α-helix satisfies the hydrogen bonding pattern described previously. The observation that the CTD might behave as a random coil or as an α-helix is of significance, and it indicates the possibility for structural rearrangements in this region, as indicated previously ( 28 ).…”
Section: Resultssupporting
confidence: 74%
“…This finding implicates a random coil to an α-helix transition in the CTD upon binding to Stx2a. This observation is supported by the molecular dynamics simulation of the TCS–CTD interaction, which indicated that the CTD has the propensity for α-helix formation in the presence of TCS ( 28 ).
Figure 8 The binding interfaces formed by the C-terminal peptides from the CTDs of P-proteins with RIPs and trGTPases.
…”
Section: Discussionmentioning
confidence: 65%
“…The catalytic center of RTA constitutes a solvent-exposed cleft on one side of the molecule that accommodates a protruding adenine base. While the molecular basis of the depurination reaction has been recognized for decades, only recently have we gained insight into how RTA is recruited to the ribosome in the first place ( 19 , 24 , 25 , 39 , 40 , 41 ). Indeed, there is now compelling evidence that the RIP activity of RTA is actually a two-step event, wherein step 1 involves interactions with ribosome by P-stalk proteins before the second engagement with the SRL.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Grela et al showed functional non-equivalence of the individual P-protein CTDs [ 69 ]. In 2021, Horbowicz-Drożdżal et al revealed that phosphorylation of the conserved C-terminal domain of ribosomal P-proteins impairs the interaction with plant toxins [ 70 ]. The study of how TCS interacts with ribosomes became a model for similar work in other RIPs [ 71 ].…”
Section: Trichosanthin As An Rrna N-glycosylasementioning
confidence: 99%